Dietary Supplement Therapies for Inflammatory Bowel Disease: Crohn’s Disease and Ulcerative Colitis - Parian, Alyssa; N. Limketkai, Berkeley (Current Pharmaceutical Design, 2016)
Inflammatory bowel disease (IBD) including ulcerative colitis and Crohn’s disease are chronic relapsing and remitting chronic diseases for which there is no cure. The treatment of IBD frequently requires immunosuppressive and biologic therapies which carry an increased risk of infections and possible malignancy. There is a continued search for safer and more natural therapies in the treatment of IBD. This review aims to summarize the most current literature on the use of dietary supplements for the treatment of IBD. Specifically, the efficacy and adverse effects of vitamin D, fish oil, probiotics, prebiotics, curcumin, Boswellia serrata, aloe vera and cannabis sativa are reviewed.
Keywords: boswellia